2023
DOI: 10.3390/healthcare11071017
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Digital Learning and Virtual Reality in Port-A Catheter Training Course for Oncology Nurses: A Mixed-Methods Study

Abstract: In-service education for oncology nurses usually adopts didactic teaching. This study investigated the effects of virtual reality (VR) and a digital learning-based Port-A-catheter educational course for oncology nurses. A mixed-methods research design was employed, with a convenience sample of 43 nurses from a regional teaching hospital in Taiwan participating. Measurements were taken at three time points: pre-test, 1st post-test, and 2nd post-test. The data was analyzed using descriptive statistics and repeat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 17 publications
(29 reference statements)
1
3
0
Order By: Relevance
“…Our study indicated that CBL- method effectively enhanced students’ individual and team operation abilities, which have also been supported by previous studies [ 7 , 8 , 33 ]. Shih et al.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Our study indicated that CBL- method effectively enhanced students’ individual and team operation abilities, which have also been supported by previous studies [ 7 , 8 , 33 ]. Shih et al.…”
Section: Discussionsupporting
confidence: 91%
“…Shih et al. reported a VR training portal-A catheter course for oncology nurses [ 8 ]. VR teaching significantly improved nurses’ port-A catheter curved needle injection skills.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations